Anti-Ulcerogenic and Toxicological Evaluation of Polyphenol Rich Extract of Cochlospermum Planchonii Roots in Tissues of Aspirin-Induced Ulcerogenic Rats - Rukayat A. Oyegoke; Mikhail O. Nafiu (AlQalam Journal of Medical and Applied Sciences, 2024)
The folkloric use of Cochlospermum planchonii roots as an anti-ulcerogenic and its safety is yet to be affirmed with scientific confirmation and this study is designed to do that. This study evaluated the anti-ulcerogenic activity and safety of polyphenol rich extract of Cochlospermum planchonii (PRECPR) roots in aspirin-induced ulcerogenic rats. These roots were processed to give dosages of 50, 100 and 150 mg/kg bodyweight. Thirty rats (138.0 ± 5.0 g) were assigned into six groups. Rats in group A (control) received 1.0 ml of distilled water. Those in groups B – F were administered 200 mg/kg body weight of aspirin and then treated with 1.0 ml of distilled water, 1.0 ml equivalent to 0.05 mg/kg body weight of omeprazole, 50, 100 and 150 mg/kg body weight of PRECPR, respectively. PRECPR dose-dependently increased (p > 0.05) nitric oxide, pH, activities of enzymes, concentrations of bilirubin, creatinine, haematological indices and decreased pepsinogen, volume and acidity of the gastric juice significantly. These results compared favourably (p < 0.05) with those of omeprazole treated group. This study provided strong indication that this extract could serve as an anti-ulcerogenic agent that is safe. إن الاستخدام الشعبي لجذور "كوكلوسبيرموم بلانشوني" كمضاد للقرحة وسلامتها لم يتم تأكيده علميًا بعد، وقد تم تصميم هذه الدراسة للقيام بذلك. قيمت هذه الدراسة النشاط المضاد للقرحة وسلامة المستخلص الغني بالبوليفينول من جذور كوكلوسبيرموم بلانشوني في الجرذان المتقرحة التي يسببها الأسبرين. تمت معالجة هذه الجذور لإعطاء جرعات 50 و100 و150 ملغم/كغم من وزن الجسم. تم تخصيص ثلاثين فأرًا (138.0 ± 5.0 جم) إلى ست مجموعات. تلقت الفئران في المجموعة (أ) (التحكم) 1.0 مل من الماء المقطر. تم إعطاء الأشخاص في المجموعات B - F 200 مجم / كجم من وزن الجسم من الأسبرين ثم عولجوا بـ 1.0 مل من الماء المقطر، 1.0 مل ما يعادل 0.05 مجم / كجم من وزن الجسم من أوميبرازول، 50 و 100 و 150 مجم / كجم من وزن الجسم من الأسبرين. بريكر، على التوالي. زاد كوكلوسبيرموم بلانشوني اعتمادًا على جرعة (P > 0.05) أكسيد النيتريك، ودرجة الحموضة، وأنشطة الإنزيمات، وتركيزات البيليروبين، والكرياتينين، ومؤشرات الدم، وانخفاض البيبسينوجين، وحجم وحموضة عصير المعدة بشكل ملحوظ. تمت مقارنة هذه النتائج بشكل إيجابي (P <0.05) مع تلك الخاصة بالمجموعة المعالجة بالأوميبرازول. قدمت هذه الدراسة إشارة قوية إلى أن هذا المستخلص يمكن أن يكون بمثابة عامل مضاد للقرحة وهو آمن.